FC 130: Kinetics of Renal Injury After Rhabdomyolysis: Implication of Innate Immune Cells and Complement Activation. (3rd May 2022) - Grunenwald, Anne; Victoria, Poillerat; Margot, Revel; Elodie, Voilin; Tania, Robe-Rybkine; Boudhabhay, Idris; Sacks, Steven H; Petitprez, Florent; Gilardin, Laurent; Roumenina, Lubka
Abstract: BACKGROUND AND AIMS: In rhabdomyolysis—characterized by massive striated muscle damage—main complication is Acute Kidney Injury (AKI) occurring in up to 50% cases. Physiopathology of rhabdomyolysis induced AKI (RIAKI) was historically described as the association of intrarenal vasoconstriction, tubular obstruction by myoglobin casts and direct tubular toxicity (by oxidative stress, lipid peroxidation). Recently, it became evident that the innate immunity also plays a role. Macrophages infiltrate contributes to direct tubular toxicity and we found activation of the complement system in patients and mice with RIAKI, in part mediated by myoglobin released heme [1 ]. Still, the mechanisms by which the innate immunity contribute to the RIAKI kidney injury and to which extend there are comparable to ischemia reperfusion injury (IRI) are not fully understood. METHOD: We performed a kinetic model of glycerol (GLY) induced RIAKI in C57BL/6 mice at 1, 3, 12, 24 hours and 7 days and analysed kidney function (biochemical parameters, histology), injury markers (Quantigene: analyse simultaneously expression of 80 genes, chosen from RIAKI transcriptomic signature (1)), complement deposits (immunofluorescence). We evaluated the abundance of tissue-infiltrating immune and stromal cell populations using gene expression (MCP counter), validated by flow cytometry. Kinetic of expression of RIAKI genes was compared to scRNAseq of IRI model [2 ]. We compared WT mice to ones deficient of the classical (C1q–/–, C4–/–), alternative (C3–/– and FB–/–) and lectin (Collectin-11-/-) pathways. Finally, we analysed complement activation fragments in the urine of 15 RIAKI patients as compared to controls ( n  = 5) and IRI patients ( n  = 5). RESULTS: Upon rhabdomyolysis, AKI in mice starts as early as 3 h post-GLY injection. Despite early upregulation of cytoprotective transcription factors (Maff, Myc, Sox9 within 3 h) and genes implicated in heme detoxification (HO1 and ferritin), both proximal and distal tubules are affected between 6 and 12 h post injury and endothelial injury is evident from 3 h. Granulocytes, monocytes and eosinophils increased in blood and infiltrated the kidney at 12 h due to preceding overexpression of chemoattractants (Cxcl1, Lgals3, Ccl2, Ccl7, Ccl12), likely by injured tubules. At 24 h, the phenotype of RIAKI kidney infiltrating inflammatory monocytes, eosinophils and resident macrophages revealed strong upregulation of C5aR1 (5x, 7x and 2x), while its levels in neutrophils tend to decrease, suggesting C5a-mediated activation. This was paralleled by intrarenal complement deposits on injured tubules and complement biomarkers in urine. To underscore the pathological relevance of complement, we found that alternative and to some extend lectin pathway deficient mice were partially protected, as opposed to mice deficient for classical pathway (Figure 1 ). Complement activation byproducts, notably Ba, C3a and C5a were increased in RIAKI patient urine as compared to control (including when normalized by proteinuria) (Figure 2 ). CONCLUSION: The kinetic of RIAKI follows the pattern of IRI acute kidney injury with specificities regarding early response to heme overload. Despite numerous protective mechanisms initiated, kidney tubules and blood vessels are rapidly affected. This results in early kidney inflammation, complement deposition and chemoattraction of immune cell with complement responsive phenotype. Complement biomarkers are increased in urine of RIAKI mice and patients alike. Our study underlines the importance to study the first hours post injury to understand the mechanisms involved in order to propose specific treatment. Complement targeting has to be explored as a therapeutic strategy in this disease.